THE CONTENT OF HEAVY METALS Pb, Cu, and Zn in ORGAN SYSTEM OF PARANG FISH (Chirocentrus dorab) AND BIANG FISH (Setipinna paxtoni) IN AIR HITAM STRAIT MERANTI ISLAND REGENCY, RIAU PROVINCE - Edy T S Sihombing; Yusni Ikhwan Siregar; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted since Juny until July 2014 in the Air Hitam Strait of Meranti Island Regency. The purpose of this study was to determine the content of heavy metals of Pb, Cu, and Zn which accumulated in organ system of Parang fish (C. dorab) and Biang fish (S. paxtoni) as the impact of sewage pollution from all human activies around the Air Hitam strait and to determine the feasibility of Parang fish (C. dorab) and Biang fish (S. paxtoni) consumption in Air Hitam strait. The results of this study showed that in Parang fish (C. dorab) Pb content was higher in the gills (5,78 µg/g), and the other heavy metals were higher too in the gills, i.e. Cu (8,68 µg/g) and Zn (39,21 µg/g) respectively. For Biang fish the heavy metals were higher in the gills, Pb (4,96 µg/g), Cu (10,03 µg/g), and Zn (33,82 µg/g) respectively. Based on heavy metal distribution, the content of Pb, Cu, and Zn in Parang fish (C.dorab) and Biang fish (S. paxtoni) at Station I was not significantly different (sig > 0,05) with Station II. Based on the  calculation, Parang fish (C. dorab) and Biang fish (S. paxtoni) from Air Hitam Strait still suitable for consumption as long as it does not exceed the specified limits.   Keywords: Pb, Cu dan Zn; C. dorab dan S. paxtoni ; Air Hitam Strait